Ameliorating Effects of Mycotoxcease (Mycotoxin Binder) on Aflatoxin M1 Excretion in Dairy Cows - Lunagariya, Pravin M; Parmar, Chirag P; Trivedi, Pankaj G; Desai, Dharmik M; Agravat, Priyam H; Sorathiya, Kalpesh K; Wadhwani, Kishan N (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This study was conducted on 16 crossbred cows to evaluate the effects of mycotoxcease on aflatoxin M1 excretion in milk, nutrient  intake and feed efficiency. The cows were divided into two groups based on milk yield, days in milk and parity in T1 (Control) and T2  (Mycotoxcease). The total mixed ration-TMR was fed ad libitum to both groups in the morning and afternoon. The T2 cows were fed  50 g of toxin binder in equal halves after mixing with 500 g of concentrate and the same quantity without toxin binder was fed to T1  cows. The dry matter, crude fat, crude protein, and metabolizable energy intake were significantly lower in T2 group. The milk and milk  component yield were not affected by toxin binder supplementation. The aflatoxin M1 excretion was 50% lower in T2 than T1 group.  Bioconcentration and carry-over percentage were also effectively reduced in T2 group. The feed efficiency and cost of feeding were lower  in T2 group. The supplementation of 50 g/day/cow toxin binder reduced aflatoxin M1 excretion, and nutrient intake, with improved  feed conversion ratio and lower cost of feeding.
Keywords: AFM1 excretion; Crossbred cows; Economics; Feed intake and efficiency; Mycotoxin binder